Inflammatory pseudotumor: the great mimicker - Patnana, Madhavi; Sevrukov, Alexander B; Elsayes, Khaled M; Viswanathan, Chitra; Lubner, Meghan; Menias, Christine O (American journal of roentgenology (1976), 2012)
The purpose of this review is to describe the pathophysiologic findings, differential diagnosis, imaging features, and management of inflammatory pseudotumor in various locations throughout the body. Inflammatory pseudotumor is a rare benign process mimicking malignant processes and has been found in almost every organ system. Radiologists should be familiar with this entity as a diagnostic consideration to avoid unnecessary surgery.